ChemInform Abstract: Application of Cooperative Iron/Copper Catalysis to a Palladium‐Free Borylation of Aryl Bromides with Pinacolborane. Issue 45 (23rd October 2014) - Labre, Flavien; Gimbert, Yves; Bannwarth, Pierre; Olivero, Sandra; Dunach, Elisabet; Chavant, Pierre Y.
Abstract The copper/iron catalytic system is operative at low temperatures and allows the borylation of aryl bromides at ‐10°C.